The current state of play of research on the social, political and legal dimensions of HIV - Paiva, Vera (Cad Saude Publica, 2015)
This paper offers a critical overview of social science research presented at the 2014 International AIDS Conference in Melbourne, Australia. In an era of major biomedical advance, the political nature of HIV remains of fundamental importance. No new development can be rolled out successfully without taking into account its social and political context, and consequences. Four main themes ran throughout the conference track on social and political research, law, policy and human rights: first, the importance of work with socially vulnerable groups, now increasingly referred to as “key populations”; second, continued recognition that actions and programs need to be tailored locally and contextually; third, the need for an urgent response to a rapidly growing epidemic of HIV among young people; and fourth, the negative effects of the growing criminalization of minority sexualities and people living with HIV. Lack of stress on human rights and community participation is resulting in poorer policy globally. A new research agenda is needed to respond to these challenges.